Factors Influencing Behavioral Intention to Participate in Family Takaful in Malaysia: An Extension of UTAUT2 Theory - Zainordin, Nur Aqilah; Engku Ali, Engku Rabiah Adawiah; Haron, Razali (Journal of Islamic Finance, 2022)
This paper aims to investigate the critical success factors that affect behavioural intention to participate in family takaful in Malaysia using the extended Unified Theory of Acceptance and the Use of Technology Model (UTAUT2) among Muslim Malaysians. This study examines the direct relationship between performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit towards behavioural intention to participate in family takaful in Malaysia. Moreover, the study explores the indirect relationship between behavioural intention and trust. This research uses quantitative methods. The data were collected from 389 respondents using a convenient sampling technique. The relationship among the variables is assessed using partial least squares structural equation modelling (PLS-SEM) for hypothesis testing. The findings showed that performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, price value are strong predictors of behavioural intention to participate in family takaful in Malaysia. Moreover, trust mediated the relationship between behavioural intention and participation in family takaful. However, social influence and habit insignificantly influence the behavioural intention to participate in family takaful in Malaysia. This study provides an extended UTAUT2 model that has never been tested in the context of family takaful. The study contributes to the field of consumer behaviour and marketing of Islamic financial products.